Combined hepatocellular cholangiocarcinoma in hepatectomy specimens: A clinicopathologic analysis - Nayana Patil; Puja Sahai; Archana Rastogi; Namita Sharma; Saggere Muralikrishna Shasthry; Amar Mukund; Shalini Thapar Laroia; Guresh Kumar; Viniyendra Pamecha; Shiv Kumar Sarin (Wolters Kluwer Medknow Publications, 2023)
Background: Combined hepatocellular-cholangiocarcinoma (cHCC-CCA) is an uncommon form of primary liver carcinoma. It is heterogenous in terms of morphology, immunohistochemistry, radiology, and clinical features; making it a challenging entity for diagnosis. Aims: The purpose of the present study was to evaluate clinicopathological characteristics of patients with cHCC-CCA. Settings and Design: Retrospective observational study. Materials and Methods: The patients diagnosed with cHCC-CC were identified from hepatic surgical specimens and were evaluated. Statistical Analysis: Survival was estimated as per Kaplan-Meier method. Results: Out of six patients, five had undergone resection while one had liver transplant. Five were male and one was female and the mean age was 52 years. Tumor markers revealed raised serum alfa-fetoprotein and CA19.9 in four and three patients, respectively. Five of the liver specimens were cirrhotic. Diagnosis was predominantly based on tumor morphology. All cases were of Allen and Lisa type B and cHCC-CCA as per WHO (2019) classification. Stem cell features <5% were noted in two cases. Immunohistochemistry for programmed death 1/programmed death ligand 1 (PD1/PDL1) was negative in both the hepatocellular and cholangiocellular components in all six cases. Mismatch repair (MMR) protein expression was retained in two and deficient in four cases. The median follow-up after surgery was 21.3 months (range, 5-46.2 months). Five patients had intrahepatic and/or extrahepatic recurrence on follow-up after surgery. The median recurrence-free survival was estimated at 13.1 months (95% CI 5.67-20.6). Three patients had received salvage treatment. The median overall survival was estimated at 20 months (95% CI 0-45.3). Conclusions: The present study highlights the role of morphology in the diagnosis of cHCC-CCA. The choice of locoregional and/or systemic therapy after surgery may be individualized based on the clinicopathological characteristics.